Filiform Polyposis Secondary to Colonic Tuberculosis Presenting as Acute Colo-Colonic Intussusception - Jacob S. Heng; Alan Baird; Marco R. Novelli; Robert N. Davidson; Rajinder P. Bhutiani (Case Reports in Surgery)
Filiform polyposis represents a rare but recognised manifestation on the varied spectrum of histopathology in colonic tuberculosis. We report a case of filiform polyposis secondary to colonic tuberculosis presenting as colo-colonic intussusception diagnosed on an abdominal computed tomography (CT) scan. The patient required urgent hemicolectomy and defunctioning ileostomy. Examination of the resected bowel lesions revealed filiform polyposis. Induced sputum samples from the patient grew Mycobacterium tuberculosis. The patient recovered well from the surgery and received treatment for tuberculosis. At last follow-up, he was awaiting the reversal of his ileostomy. The protean nature of histological findings in colonic tuberculosis and other current diagnostic challenges are discussed. The importance of maintaining a high index of suspicion for colonic tuberculosis and instituting early treatment is highlighted in this case.